Influence of condensate corrosion on tensile and fatigue properties of brazed stainless steel joints AISI 304L/BNi‐2 for automotive exhaust systems: Einfluss von Kondensatkorrosion auf die Zug‐ und Ermüdungseigenschaften der Edelstahllötverbindungen 1.4307/Ni 620 für Automobilabgassysteme. Issue 3 (27th March 2018) - Schmiedt, A.; Manka, M.; Tillmann, W.; Walther, F.
Abstract: Materials and brazed joints for automotive exhaust systems have to resist the corrosive nature of aggressive exhaust gases as well as static and cyclic loads. In the present study, the influence of condensate corrosion according to VDA 230–214, with an ageing duration of up to 6 weeks, on the tensile and fatigue properties of stainless steel AISI 304L and brazed AISI 304L/BNi‐2 joints is investigated. In relation to the as‐received condition, the ultimate tensile strength is decreased down to 58 % and a reduction of the fatigue strength at 2⋅10 6 cycles down to 22 % is determined for brazed specimens, pre‐corroded for 6 weeks. In contrast to the brazed stainless steel joints, the condensate corrosion does not influence the tensile properties of the AISI 304L base material. Stress concentrations at the corrosion‐dependent circumferential grooves at the brazing seam are evaluated by stress intensity factors, which are well appropriate to characterise the fatigue behaviour depending on the corrosion condition.